2005
DOI: 10.1246/cl.2005.428
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous Nickel Oxide Nanofiber

Abstract: Porous nickel oxide (NiO) nanofibers, structured with and composed of linearly oriented NiO nanoparticles, were synthesized via a simple method using a solution containing ethanol, H2O, NiCl2, and P123 (Pluronic P123, a triblock copolymer H(OCH2CH2)20(OCH(CH3)CH2)70(OCH2)20OH). By adjusting the concentration of P123, this method allows for the control of the fiber morphology and the nanoparticle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…This suggests that at small applied biases (close to JSC) the overpotential for electrolyte reduction at the cathode is sufficiently large that the system is driven by the photoanode. This phenomenon has also been observed by other authors when the photoelectrodes are not current matched [28,29], but the maximum power point seems to inevitably reside in a voltage range where both photoelectrodes are the primary elements driving current flow (rather than dark processes). Developments in pDSC device efficiency are addressed below in Section 2.1 and show a rapid and dramatic increase since this first report.…”
Section: Incident Photon To Charge Carrier Efficiency -Ipce) Using Ansupporting
confidence: 81%
See 2 more Smart Citations
“…This suggests that at small applied biases (close to JSC) the overpotential for electrolyte reduction at the cathode is sufficiently large that the system is driven by the photoanode. This phenomenon has also been observed by other authors when the photoelectrodes are not current matched [28,29], but the maximum power point seems to inevitably reside in a voltage range where both photoelectrodes are the primary elements driving current flow (rather than dark processes). Developments in pDSC device efficiency are addressed below in Section 2.1 and show a rapid and dramatic increase since this first report.…”
Section: Incident Photon To Charge Carrier Efficiency -Ipce) Using Ansupporting
confidence: 81%
“…The first paper on pDSCs, as discussed above, reported only very low efficiencies [5]. The next report on pDSC did not appear for another 6 years, when Nakasa et al applied Coumarin 343 (C343) as a sensitizer [29].…”
Section: Overview Of Pdsc Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…The proof of concept of this strategy has been reported in 2000, using N719 as a sensitizer on TiO 2 for the photoanode and erythrosine B as a sensitizer on NiO for the photocathode [98]. The performance of this system has been improved by more than 50% (from η = 0.39% to 0.66% under air mass (AM) 1.5) by using a mesoporous NiO film of higher quality [99].…”
Section: P-type Inorganic Hole Transport Materials For Pscsmentioning
confidence: 99%
“…Recently, significant improvements on NiO-based PSCs were made by doping the NiO thin film or modifying the NiO/perovskite interface heterojunction [98][99][100][101][102]. Kim et al demonstrated a high-efficiency planar PSC by using solution-processed copper (Cu)-doped NiO x (Cu:NiO x ) as a HTM [122].…”
Section: Planar Nio-based P-i-n Pscsmentioning
confidence: 99%